Maximum Entropy Bootstrap for Time Series: The meboot R Package - Vinod, Hrishikesh D.; Lopez-de-Lacalle, Javier (Journal of Statistical Software, 2009)
The maximum entropy bootstrap is an algorithm that creates an ensemble for time series inference. Stationarity is not required and the ensemble satisfies the ergodic theorem and the central limit theorem. The meboot R package implements such algorithm. This document introduces the procedure and illustrates its scope by means of several guided applications.